Mechanical characterization and fatigue assessment of wire and arc additively manufactured HSLA steel parts - Rodideal, Nicolae (2022)
info:eu-repo/grantAgreement/FCT/6817 - DCRRNI ID/UIDB%2F00667%2F2020/PT The authors gratefully acknowledge A.J. Maltez - Sociedade Metalúrgica Lda for test specimen machining. Publisher Copyright: © 2022 Elsevier Ltd